Intertext As a Form of Communication Between The Author and The Reader in Taras Shevchenko's Diary - Лебідь-Гребенюк, Євгенія (Київський національний університет імені Тараса Шевченка, 2026)
Background. The relevance of the research is determined by the need to reimagine Taras Shevchenko's diary in modern Shevchenko studies through the prism of his self presentation strategies and intellectual resistance within colonial discourse. The study of intertext as a specific form of communication allows us to trace the author's transformation from an object of imperial influence into an active subject of cultural dialogue. Of particular importance is the analysis of the ironic function of the intertext and the incorporation of evaluative descriptions through a system of allusions and quotations, which allowed the author to distance himself from the absurdity of despotism and create oppositional meanings, acquires special importance. The study of the intertextual nature of the diary is crucial for understanding how Shevchenko built a space of inner freedom through dialogue with culture, literature and his readers. The purpose of this article is to investigate the peculiarities of the functioning of the intertext in Shevchenko's diary and to reveal its role in interaction with the reader.Methods. The research uses a multidisciplinary approach that integrates the methods of intertextual analysis (Y. Kristeva, R. Barth), receptive aesthetics (V. Iser, G. R. Jauss), cultural semiotics (U. Eco) and narratology (M. Bakhtin). This methodological framework allows us to analyze the interaction between the real / implied reader and the author through a system of cultural codes. The intertextual method is used to identify and classify "foreign words" in Shevchenko's text. The method of contextual analysis makes it possible to compare intertextual elements with the historical and biographical circumstances of the writing of the diary (for example, the period of stay in the Novopetrov Fort). The communicativepragmatic method makes it possible to investigate the intertext as a tool for transferring meanings from the author to the potential addressee, considering individual borrowings as an act of conscious communication. The receptiveaesthetic method is aimed at researching possible reader interaction with the text. The structural-semantic approach is used to study the role of quotations in the construction of a coherent composition of a diary, where they often play the role of content nodes that unite different entries into a single narrative. The descriptiveanalytical method serves to systematize and consistently present the results of the study of the author's interaction with the reader in the text.Results. In the conditions of existential and partly social isolation during exile, the intertext in Shevchenko's diary functions as an important mechanism for overcoming intellectual loneliness and expressing spiritual resistance through biblical and cultural allusions, reminiscences. The use of intertextual references enables the author to guide the reader's attention, ingaging them in a collaborative decoding of meanings and emotional empathy. Intertextuality creates a space for intellectual freedom within the Journal, where intertextual references serve to counter imperial pressure and universalize the experience of personal resilience. The study identifies and substantiates four levels of intertextual interaction in the text of the diary: sacred universal, intellectual-selective, oppositional-ironic and intermedial.Conclusions. Shevchenko's Journal is a unique diary text in which the boundary between an ego-document and a literary diary is blurred. The author's conscious designation of addressees at the very beginning of the text transforms the auto-communicative act into a space of open dialogue. This intentional openness, reinforced by implicit communicability, turns private chronicles into a tool for shaping a shared axiological field between the author and like-minded contemporaries. Furthermore, the plasticity of the genre nature of the work allows it to be viewed not only as a means of self-reflection, but also as a strategically constructed appeal to a wide range of recipients ‒ from the immediate environment to future readers. Ultimately, intertextuality in the diary becomes a tool for overcoming intellectual isolation.

Вступ. Актуальність теми зумовлена необхідністю переосмислення у сучасному шевченкознавстві щоденника Тараса Шевченка через призму стратегій його самопрезентації та інтелектуального спротиву в умовах колоніального дискурсу. Вивчення інтертексту як специфічної форми комунікації дозволяє простежити трансформацію автора з об'єкта імперського впливу ("рядовой Т. Шевченко") на активного суб'єкта культурного діалогу ("художник Т. Шевченко"). Особливого значення набуває аналіз іронічної функції інтертексту та залучення оцінних дескрипцій через систему алюзій і цитат, які дозволяли автору дистанціюватися від абсурду царської деспотії та створювати опозиційні смисли. Вивчення інтертекстуальної природи щоденника стає визначальним для розуміння того, як через діалог із культурою, літературою та своїми читачами Шевченко вибудовував простір внутрішньої свободи. Відповідно, мета нашої статті ‒ дослідити особливості функціонування інтертексту у щоденнику Шевченка, розкрити його роль у взаємодії з читачем.Методи. Методологічною основою дослідження стали прийоми інтертекстуального та контекстуального аналізу, комунікативно-прагматичний, рецептивно-естетичний і описово-аналітичний методи.Результати. В умовах екзистенційної та частково соціальної ізоляції заслання інтертекст у щоденнику Шевченка функціонує як важливий механізм подолання інтелектуальної самотності, вираження духовного опору через біблійні та культурні алюзії, ремінісценції. Використання інтертекстуальних вставок дозволяє автору керувати увагою читача, залучаючи його до спільного декодування сенсів та емоційного співпереживання. Інтертекстуальність відкриває у "Журналі" простір інтелектуальної свободи, де запозичені тексти стають засобом подолання імперського тиску та універсалізації досвіду особистої стійкості. Визначено та обґрунтовано чотири рівні інтертекстуальної взаємодії у тексті щоденника: сакрально-універсальний, інтелектуально-селективний, опозиційно-іронічний та інтермедіальний.Висновик. Аналіз комунікативних функцій інтертексту у щоденнику Тараса Шевченка дозволяє зробити висновок, що взаємодія з читачем реалізується через залучення його до процесу спільного декодування смислів та активізацію авторських інтенцій у межах відкритого діалогу. Використання інтертекстуальних елементів трансформує приватну рефлексію у стратегічну комунікацію, яка консолідує рецепієнта довкола спільних аксіологічних орієнтирів та ідей інтелектуальної резистентності.
Інтертекст як форма комунікації між автором і читачем у щоденнику Тараса Шевченка
Keywords: diary literature; communicative strategy; intertext; author; reader; dialogism; діарна література; інтертекст; комунікативна стратегія; автор; читач; діалогічність